Preoperative management and postoperative complications associated with transoral decompression for the upper cervical spine - Wenqiang Li; Bingjin Wang; Xiaobo Feng; Wenbin Hua; Cao Yang (BMC Musculoskeletal Disorders, 2022)
Abstract Purpose This review aimed to describe the preoperative management and postoperative complications associated with transoral decompression of the upper cervical spine, and to clarify the risk factors, related issues and complication management. Methods Studies on transoral decompression for the upper cervical spine were reviewed systematically. The preoperative management and postoperative complications associated with transoral decompression for upper cervical deformities were analyzed. Results Evidence suggests that preoperative management in patients undergoing transoral decompression for the upper cervical spine is closely related to the occurrence of postoperative complications. Hence, preoperative surgical planning, preoperative preparation, and oral nursing care should be seriously considered in these patients. Moreover, while being established as an effective and safe method, transoral decompression is associated with several postoperative complications, which could be prevented by elaborate preoperative management, improved surgical skills, and appropriate precautionary measures. Conclusions The effectiveness and safety of transoral decompression has been improved by the constant development of operative techniques and advanced auxiliary diagnostic and therapeutic methods, with the understanding of the anatomical structure of the craniocervical joint. Therefore, the incidence rates of postoperative complications have decreased. The application of individualized anterior implants and less-invasive endoscopic endonasal approach has improved the effectiveness of transoral decompression and reduced the associated complications.